2014
DOI: 10.1155/2014/636725
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Aligned ZnO Nanorod Arrays on Sn-Doped ZnO Thin Films by Sonicated Sol-Gel Immersion Fabricated for Dye-Sensitized Solar Cell

Abstract: Aligned ZnO Nanorod arrays are deposited on the Sn-doped ZnO thin film via sonicated sol-gel immersion method. The structural, optical, and electrical properties of the Sn-doped ZnO thin films were investigated. Results show that the Sn-doped ZnO thin films with small grain size (~20 nm), high average transmittance (96%) in visible region, and good resistivity7.7 × 102 Ω·cm are obtained for 2 at.% Sn doping concentration. The aligned ZnO nanorod arrays with large surface area were also obtained for 2 at.% Sn-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Then, the solution was continuously stirred for 3 hours at room temperature and then poured into a container with an Al: ZnO seed coated glass substrate inserted into the container. The immersion process was done by immersing sealed vessels inside the water bath for 60 minutes at 95°C for nanorod growth [23]. For the second immersion process, GO solution with different concentrations (0, 0.2, 0.3, 0.4, 0.5, and 0.6mg/ml GO) was poured into each vessel onto the ZnO nanorods.…”
Section: Methodology 21 Growth Processmentioning
confidence: 99%
“…Then, the solution was continuously stirred for 3 hours at room temperature and then poured into a container with an Al: ZnO seed coated glass substrate inserted into the container. The immersion process was done by immersing sealed vessels inside the water bath for 60 minutes at 95°C for nanorod growth [23]. For the second immersion process, GO solution with different concentrations (0, 0.2, 0.3, 0.4, 0.5, and 0.6mg/ml GO) was poured into each vessel onto the ZnO nanorods.…”
Section: Methodology 21 Growth Processmentioning
confidence: 99%
“…Sol-gel immersion has high quality of aligned ZnO nanorods. This method was started with preparing the solution by a sonicated sol-gel and immersion method to grow ZnO nanorods [70]. Moreover, this method has low cost production, simplicity, capability to control the growth of ZnO nanorods and low temperature deposition process.…”
Section: Effect Of Zno and Tio2 Layer In The Photoanode Propertiesmentioning
confidence: 99%
“…In 2013, Research on the fabrication of MEH-PPV [2-methoxy-5-(2 -ethylhexyloxy)p-phenylenevinylene]/Al:ZnO nanorod arrays based on ordered bulk heterojunction hybrid solar cells) has resulted in high performance (Jsc = 5.32 mA/cm 2 , Voc = 195 mV, FF = 27.71%,and EFF = 0.287%), an average optical transmission of approximately 78%, and an improved absorption coefficient compared to the catalyst layer seeded [12]. On the other hand, in 2014, an Experimental study of aligned ZnO nanorods on ZnO thin films doped with 2% Sn yielded high transmittance in the visible region, a large area with longer aligned ZnO nanorods, and improved performance (short-circuit current density Jsc = 2.840 mA/cm 2 , open-circuit voltage Voc = 0.552, fill factor FF = 0.381, and the power conversion efficiency of 0.599%) compared to the undoped film [13]. Also, in 2015, Jalal Rouhi et al showed that vertically aligned ZnO-ZnS core-shell nanocone arrays can be useful for optoelectronic devices due to a good surface-to-volume ratio, good electrical performance (Jsc = 12.2 mA/cm 2 , Voc = 0.68 V, and FF = 0.49), better light trapping, and longer life than the other structures [14].…”
Section: Introductionmentioning
confidence: 99%